Charges for Oral Health Care During a Period of Economic Growth in the US: 1987-96 - Amit Chattopadhyay, MDS, MPH; Gary D. Slade, BDSc, DDPH, PhD; Daniel A. Shugars, DDS, PhD (2003)
This study aimed to provide estimates of amounts charged for dental care during 1996 for the US adult population and its major sociodemographic subgroups, and to evaluate whether charges had increased since 1987